2021
DOI: 10.1177/1087054721997553
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation Intervention Effectiveness to Improve Social Skills in Young People with ADHD: A Meta-Analysis

Abstract: Objective: Attention Deficit Hyperactivity Disorder (ADHD) can be associated with limited understanding of the condition and poor social skills. Some evidence favors a psychoeducational approach, but little is known about the effectiveness of psychoeducation. Methods: Systematic review and meta-analysis of studies assessing psychoeducational interventions that aim to improve social skills of young people with ADHD. Results: Ten studies, including 943 participants, reported across 13 papers met the inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…The rationale of psychoeducation is to educate about the course of the disorder, its causes and maintenance factors, treatment options, and also to focus on the patient's individual strengths, resources and opportunities for development. Although psychoeducation generally shows promising results, the overall study quality is considered relatively low, and few studies have systematically examined effects in adult ADHD (Montoya et al, 2011;Powell et al, 2022;Vaag et al, 2019). Consequently, the European Network Adult ADHD considers psychoeducation to be effective in principle, but also emphasizes the need to further develop structured psychoeducation programs (Kooij et al, 2010;Kooij et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale of psychoeducation is to educate about the course of the disorder, its causes and maintenance factors, treatment options, and also to focus on the patient's individual strengths, resources and opportunities for development. Although psychoeducation generally shows promising results, the overall study quality is considered relatively low, and few studies have systematically examined effects in adult ADHD (Montoya et al, 2011;Powell et al, 2022;Vaag et al, 2019). Consequently, the European Network Adult ADHD considers psychoeducation to be effective in principle, but also emphasizes the need to further develop structured psychoeducation programs (Kooij et al, 2010;Kooij et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite existing evidence, there is little age-appropriate information or interventions that are accessible and available for young people with ADHD (Powell et al 2021). It is also important to involve young people and families in the co-design such information (Sanders and Stappers 2008) as codesigned interventions are more likely to be accepted and lead to impact (Greenhalgh et al 2016), and very little co-designed materials for this population exists.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of psychoeducation for individuals with ADHD depends on other comorbid mental disabilities, socio-demographic factors, the severity of ADHD, gender, and parental involvement. Psychoeducation helps children with ADHD gain socializing knowledge but does not improve social skills if the individual has inadequate exposure to society, making them less experience and having limited practice in socialising (Powell et al, 2021). Other studies have also reported that the social problems among children with ADHD are related to inconsistent social training and a lack of social knowledge (Aduen et al, 2018).…”
Section: Effectiveness Of Psychoeducation Programmesmentioning
confidence: 99%